Modeling the Hydrodynamic Pressure Field and Wake Field Characteristics of an Underwater Vehicle and Studying Their Correlation - Peihao Li; Hui Deng; Bingrui Xu; Weixue Xia; Wenbin Yi (Journal of Marine Science and Engineering)
The hydrodynamic pressure field and wake field generated by an advancing underwater vehicle are used as key factors for its detection and identification. In this paper, a numerical method is established based on the Reynolds-averaged Navier–Stokes equation. Following grid convergence verification for seven kinds of grids, the differences between the hydrodynamic pressure field and wake field are investigated using the gridding method and turbulence model. Subsequently, on a validation basis, the characteristics and correlation of the hydrodynamic pressure field and wake field for an underwater vehicle at different water depths are studied, showing that the SST turbulence model is applicable to underwater vehicle hydrodynamic pressure fields with low grid requirements. A high grid density and the LES turbulence model are needed to accurately capture information about the wake field’s flow field. As the underwater vehicle approaches the bottom, the hydrodynamic pressure field characteristics change significantly, and the wake field characteristics do not significantly change. In the region behind the hull, the influence of the wake field on the hydrodynamic pressure field is complex, but it has a short acting distance. The correlation in the area behind the hull is crucial for identifying, detecting, and tracking targets.